Intracellular membrane traffic at high resolution. - Weering, v; Brown, E; Sharp, T; Mantell, J; Cullen, P; Verkade, P (2010)
Membrane traffic between organelles is essential for a multitude of processes that maintain cell homeostasis. Many steps in these tightly regulated trafficking pathways take place in microdomains on the membranes of organelles, which require analysis at nanometer resolution. Electron microscopy (EM) can visualize these processes in detail and is mainly responsible for our current view of morphology on the subcellular level. This review discusses how EM can be applied to solve many questions of intracellular membrane traffic, with a focus on the endosomal system. We describe the expansion of the technique from purely morphological analysis to cryo-immuno-EM, correlative light electron microscopy (CLEM), and 3D electron tomography. In this review we go into some technical details of these various techniques. Furthermore, we provide a full protocol for immunolabeling on Lowicryl sections of high-pressure frozen cells as well as a detailed description of a simple CLEM method that can be applied to answer many membrane trafficking questions. We believe that these EM-based techniques are important tools to expand our understanding of the molecular details of endosomal sorting and intracellular membrane traffic in general.